Copper nanoparticles induce early fibrotic changes in the liver via TGF-β/Smad signaling and cause immunosuppressive effects in rats. Issue 6 (3rd July 2018) - Lee, In-Chul; Ko, Je-Won; Park, Sung-Hyeuk; Shin, Na-Rae; Shin, In-Sik; Moon, Changjong; Kim, Sung-Ho; Yun, Won-Kee; Kim, Hyoung-Chin; Kim, Jong-Choon
Abstract: Copper nanoparticles (Cu NPs) have various uses, including as additives in polymers/plastics, lubricants for metallic coating, and biomedical applications. We investigated the role of transforming growth factor (TGF)-β1 signaling in hepatic damage caused by Cu NPs and explored the effects of a 28-day repeated oral administration to Cu NPs on the immune response. The exposure to Cu NPs caused a dose-dependent increase in Cu levels in the liver and spleen. Cu NPs caused hepatic damage and markedly increased oxidative stress in liver tissues. Cu NPs induced activation of TGF-β1/Smad signaling by induction of vascular endothelial growth factor and matrix metalloproteinase-9. Exposure to Cu NPs also induced activation of Smad-independent pathways, phosphorylation of mitogen-activated protein kinases (MAPKs) and Akt/FoxO3. Consistent with the activation of TGF-β1/Smad-dependent and -independent pathways, Cu NPs markedly increased the deposition and induction of extracellular matrix components, α-smooth muscle actin, and collagens in liver tissues. In addition, repeated exposure to Cu NPs suppressed the proliferation of mitogenically stimulated T- or B-lymphocytes and decreased CD3 + (particularly, CD3 + CD4 + CD8 − ) and CD45 + population, followed by decreased levels of immunoglobulins and Th1/Th2 type cytokines. Collectively, Cu NPs caused hepatic damage and induced pro-fibrotic changes, which were closely related to the activation of oxidative stress-mediated TGF-β1/Smad-dependent and -independent pathways (MAPKs and Akt/FoxO3). We confirmed the immunosuppressive effect of Cu NPs via the inhibition of mitogen-stimulated spleen-derived lymphocyte proliferation and suppression of B- or T-lymphocyte-mediated immune responses.